The Influence of Celebrity Endorser 'Tasya Farasya' and Big Five Personality on Impulsive Buying in Surabaya (Case Study of Consumers of Somethinc Skincare Products) - Cantika Aura Jahzy; Indah Respati Kusumasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The increasing use of celebrity endorsers and personalized marketing in the beauty industry has influenced consumer buying behavior, particularly impulsive buying. This study aims to examine the effect of Celebrity Endorser and Big Five Personality on Impulsive Buying among Somethinc skincare consumers in Surabaya. The research addresses whether these variables influence impulsive buying both simultaneously and partially. A quantitative method with an associative approach was applied. Data were collected through questionnaires distributed to 100 respondents using purposive sampling. The analysis involved validity, reliability, classical assumption tests, multiple linear regression, hypothesis testing (t-test and F-test), and the coefficient of determination (R²). The results show that Celebrity Endorser and Big Five Personality simultaneously have a significant effect on impulsive buying. Partially, Celebrity Endorser and Big Five Personality both have significant effects. These findings highlight the importance of combining external marketing stimuli and internal personality traits in influencing impulsive buying behavior.